PERENCANAAN JALUR EVAKUASI KEBAKARAN YANG EFISIEN UNTUK FASILITAS PERAWATAN RUMAH SAKIT DENGAN MENGGUNAKAN ALGORITMA DIJKSTRA - Safutra, Nur Ihwan; Fole, Asrul; Gunawan, Alam; Hafid, Muhammad Fachry; Ahmad, Arfandi; Herdianzah, Yan (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
This study aims to design fire evacuation routes using the Dijkstra Algorithm at RSUD I Lagaligo in East Luwu Regency, as part of the building renovation to improve service quality. The Dijkstra Algorithm was chosen for its ability to determine the shortest path from one point to another in a graph. This research employs systematic and logical data analysis techniques to obtain the closest evacuation routes. The results show a significant decrease in evacuation distance after the implementation of the Dijkstra algorithm, enhancing travel efficiency while maintaining consistent gathering points, except for some routes that experience changes in gathering points.